Analysis of the State of Energy Metabolism and Autonomic Nervous System of Children and Adolescents in the Aral Sea Region (Republic Of Karakalpakstan) (Texas Journal of Multidisciplinary Studies, 2023)
This work explains that, pupils from grades 1 through 11 at school No. 8 in the city of Nukus, the Republic of Karakalpakstan, had their minimum and maximum heart rates measured at 83.73±4.36 beats per minute (bpm) for boys and 79.32±2.26 beats per minute (bpm) for girls. They also had their systolic blood pressure measured at 85.16±4.15 beats per minute (bpm) for boys and 89.37±4.09 beats per minute (bpm) for girls. The Robinson index's minimum/maximum values for boys are 73.43±4.26/104.18±2.37, and 75.38±3.17/102.43±5.27 for girls, respectively. The mechanisms of energy exchange in the body were rated as "excellent" in the overall condition of boys and girls aged 7 to 10, and "poor" in the age range of 11 to 17 years. A minimum/maximum range of 23.18±1.05/42.32±1.24 was seen for the Kerdo index values in investigations including school children in grades 1-11. Contrarily, the autonomic nervous system in schoolchildren was entirely "sympathetic" meaning that the sympathetic nervous system was given primacy. For boys, this was 16.80±0.89 and for girls, it was 38.50±1.05.